Qué factores explican la pobreza multidimensional en Espa\~na? Una aproximación a través de los modelos de ecuaciones estructurales - Carlos Poza Lara; José Andrés Fernández Cornejo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– The aim of this study is to present the most important factors that explain multidimensional poverty in Spain, highlighting the relationships between the explanatory elements themselves in the spirit of enhancing the effects of poverty policy. For this purpose, we have designed a Structural Equation Model using the enlarged sample of Household Panel European Union in 2000. Education and employment seem to be the most determining latent construct. In particular, the level of education and the type of employment contract are the most important variables to explain multidimensional poverty.
Keywords: H31; H75; I32; 330; multidimensional poverty; structural equations